QSPR Analysis of Novel Indices with Priority Polycyclic Aromatic Hydrocarbons(PAHs) - et. al., C.Tamilarasi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, proposed degree-based topological index,FORAN index = and its corresponding neighborhood degree-sum index NFORAN index = are established by known property dependence relationships(Degeneracy test with eighteen octane isomers). And developed linear models based on n-octane isomers &sixteen priority Polycyclic Aromatic Hydrocarbons(PAHs) byQSPR study.